Pengaruh Kepemimpinan, Kompensasi Finansial, dan Komitmen terhadap Kinerja Pegawai dengan Mediasi Budaya Organisasi di Biro Perencanaan dan Administrasi Lemdiklat Polri - Putra, I Kadek Alit Suwardana; Purnomo, Hadi; Sukiman, Sukiman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to determine and analyze the effect of leadership on organizational culture. To determine and analyze the effect of financial compensation on organizational culture. To determine and analyze the effect of organizational commitment on organizational culture. To determine and analyze the effect of leadership on employee performance. To determine and analyze the effect of financial compensation on employee performance. To determine and analyze the effect of organizational commitment on employee performance. To determine and analyze the effect of organizational culture on employee performance at the Planning and Administration Bureau of the Education and Training Institute of the Indonesian National Police. This study uses a quantitative approach with descriptive and associative research types. The population studied consisted of 60 employees of the Renmin Bureau of the Indonesian National Police Education and Training Institute. The sampling technique used was total sampling. The data collection techniques used in this study were questionnaire distribution and observation. The analysis technique used in this study was the SmartPLS 3.0 program. The results of the study show that: 1) There is no significant effect of leadership on organizational culture. 2) There is no significant effect of financial compensation on organizational culture. 3) There is a positive and significant effect of organizational commitment on organizational culture. 4) There is a positive and significant effect of leadership on employee performance. 5) There is a positive and significant effect of financial compensation on employee performance. 6) There is a positive and significant effect of organizational commitment on employee performance. 7) There is a positive and significant effect of organizational culture on employee performance.